Development and data bank organization for automatic selection of cutter conditions for lathering - Todić, Velimir (Journal of Production Engineering, 1990)
Automatic selection of cutter conditions during technology processes projection and optimization, represent significant contribution to whole efficiency increasing of technological preparation for production. Development and organization of data bank for culture conditions requires application of all rules on which is high-quality and reliability use of these information systems are based. This data bank enables automatic selection of cutter conditions. Rules which enable permanent data bank for cutter conditions with new data addition and rules which enable and reliability of selected conditions, are the most important. These new data are in harmony with possibilities which are defined by hew cutter tools, new mechanical materials, mechanical treatment conditions and contemporary manufacturing systems. In the paper, the rules and the logic of cutter conditions data bank for lathering development, organization and use are showed. This data bank is the part of technological data bank which enables selection of cutter conditions on the interactive principle.